Is Social Media Having any Impact on Teaching and Learning Practices? - Wilson, Sharon (Global Journal of Social Sciences Studies, 2021)
The study has focused on determining the impact of social media on the teaching and learning practices. The design of this study is quantitative as the data has been gathered from the students and teachers through survey questionnaire. The number of respondents were 280. The analysis was carried out on SmartPLS in which the Structural Equation Modelling (PLS-SEM) was used. Therefore, the data was analysed using measurement model and path assessment with reflective constructs. The results revealed that there is overall significant effect of collaboration and interaction, creativity and knowledge sharing on learning practices. On the other hand, creativity, knowledge sharing and use of SNS had significant influence over teaching practices. The study is limited to the educational practices as it determines the effect of SNS on the teaching and learning practices.